2005
DOI: 10.1021/om049107b
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear and Binuclear Cyclopentadienyl Oxo Molybdenum and Tungsten Complexes:  Syntheses and Applications in Olefin Epoxidation Catalysis

Abstract: New half-sandwich molybdenum complexes [Mo(CpBz)Cl 2 (O)] (1), [{Mo(CpBz)(O) 2 } 2 (µ−O)] (5) and [Mo(CpBz)Cl 2 ] 2 (6) (CpBz = C 5 (CH 2 Ph) 5 ), the tungsten derivative [W(CpBz)Cl(O) 2 ] (3) and a high yield synthesis of [Mo(CpBz)Cl(O) 2 ] (2), are described. The molecular structures and cyclic voltammetry measurements of 1 and 2 and a comparative study of various molybdenum dioxo complexes as olefin epoxidation catalyst precursors are also presented. The performance of [Mo(CpPr i 4 )Cl(O) 2 ] (9) as cyclooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 33 publications
2
65
2
Order By: Relevance
“…Calculations on this system may also be considered to model the action of other [Cp*MoO 2 X] catalysts (X = CH 3 or Cp*MoO 3 ). [38][39][40][41] These molecules are excellent epoxidation catalysts, provided TBHP is used as the oxidant and the solvent is apolar. [42] Chloroform is frequently used, therefore the calculations have been carried out by introducing the solvent effect by the CPCM in CHCl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations on this system may also be considered to model the action of other [Cp*MoO 2 X] catalysts (X = CH 3 or Cp*MoO 3 ). [38][39][40][41] These molecules are excellent epoxidation catalysts, provided TBHP is used as the oxidant and the solvent is apolar. [42] Chloroform is frequently used, therefore the calculations have been carried out by introducing the solvent effect by the CPCM in CHCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] In a recent collaborative study, some of us showed that the dinuclear oxido-bridged [Cp # 2 Mo 2 O 5 ] systems are also catalytically active when using TBHP in an organic solvent, and are active with the same reagent under aqueous biphasic conditions. [41] However, they do not yield significant amounts of epoxidation product when TBHP is replaced by H 2 O 2 . [42] Only recently, the use of MeOOH as a model of the tBuOOH reagent has been considered in a theoretical study, based on the compound [MoO 2 Br 2 (MeN=CHCH=NMe)] as the catalyst.…”
Section: Cp*moo(oh)a C H T U N G T R E N N U N G (Oor)cl] or [Cp*moo(mentioning
confidence: 99%
“…Solvent removal afforded a red microcrystalline solid in 91 % yield (1.54 g, 1.15 mmol). 1 General Procedures for X-ray Crystallography: Pertinent details for the individual compounds can be found in Tables 5 and 6. Crystallographic data for compounds 4, 6 and 7 were collected using graphite-monochromated Mo-K α radiation (λ = 0.71069 Å) with a Bruker AXS-KAPPA APEX II area detector diffractometer equipped with an Oxford Cryosystem open-flow nitrogen cryostat; data were collected at 150 K for compounds 4 and 6 and at 130 K for compound 7.…”
Section: Methodsmentioning
confidence: 99%
“…A comparison of [MoCpЈ(O) 2 Cl] (CpЈ = Cp, Cp*, CpiPr 4 , CpBz) complexes showed that the CpBz derivative leads to the most active and stable catalyst system when activated with tBuOOH. [1] Moreover, chlorination reactions of low oxidation-state (CpBz)carbonylmolybdenum and -tungsten complexes also differ from those of their Cp and Cp* analogues. In particular, the reactions of [MoCpBz(CO) 3 the application of hydrido complexes of general formula [MCp(CO) 2 L(H)] (M = Mo, W; L = CO, PR 3 ) as hydrogenation catalysts of ketones and aldehydes has recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is a rare example of a third-row metal radical with an NHC ligand [132]. Its crystal structure shows a three legged piano stool configuration with W- -44(a,b) give similarly high activity for olefin epoxidation as CpMo(CO) 3 X (X = Cl, Br, CH 3 ) [138][139][140][141][142][143][144][145]. Such strong activity is attributed to the high stability of the Mo-C carbene bond in these ionic complexes under oxidative conditions.…”
Section: The Reaction Intermediate [(Ime)h] + [Cpw(co) 2 (Pph 3 )] -(mentioning
confidence: 99%